MENGUJI NETRALITAS ILMU PENGETAHUAN - SYAIFUL BAKRI (Sekolah Tinggi Ilmu Syariah Darul Falah Bondowoso, 2021)
This paper discusses in detail about science as the only weapon of life civilization. In its development, science has a state of uncertainty. In this uncertainty, as an independent science, it is required to be able to submit to its rules. Armed with knowledge, humans are capable of creating civilizations and with knowledge humans can create havoc in the pages of their lives. Thus, the neutral and non-neutral role of science in human life becomes a big question mark.